COVID-19 EPIDEMIOLOGICAL SCENARIO IN ICAPUÍ/CE - de Oliveira Gomes , Jamille; Faustino Souza , Lucielmo; Souza do Amaral, Sandy; Franklin Sousa de Freitas, Raylka; Pereira Nobre , Micael; Freitas Barros , Jônatas; Sousa dos Santos, Emanuela (Cadernos ESP, 2024)
To analyze the epidemiological scenario of COVID-19 in the city of Icapuí, in the interior of Ceará, from 2020 to 2022. To conduct this research, epidemiological bulletins from public domains were consulted. This study showed that most COVID-19 notifications occurred in people aged 30 to 39. The number of confirmed cases of the disease increased significantly in 2021, but decreased in 2022, possibly due to the start of vaccination. It is essential that health authorities continue to promote awareness campaigns on the importance of prevention measures and vaccination to control the spread of COVID-19.